The non-place of the Brazilian northeastern migrant in Essa terra, by Antonio Torres - Goncalves, Rogerio Gustavo [UNESP] (Univ Estadual Paulista-unesp, 2017)
This paper analyzes, in the novel Essa terra, by Antonio Torres, the journey of the character Nelo, who migrates to Sao Paulo in search of opportunities for social mobility, returning twenty years later to his homeland, in the backwoods of Bahia, where he ends up committing suicide. From the consideration of the individual story of this character as a representation of a collectivity, this text discusses the pessimistic view that the novel transmits about the condition of the northeastern migrant in Brazil, for whom there is no place in society. The narrative discusses the backcountry man situation, who is looking, with the flight to the cities, for a way to escape drought and misery. On the other hand, it also focuses on the circumstances arising from the migration process, such as the marginalization of the poor northeastern man in urban space. On the journey of the character, we evaluate as well the psychological consequences of the social and cultural influence process undergone by him from the contact with another reality, such as the impossibility of readaptation to the place of origin. Leaving Nelo in a state of deterritorialization in relation to the backwoods and not belonging in relation to the city, this relativized space places him in a kind of threshold zone, triggering the identity crisis and the subsequent suicide of the character.
Keywords: Antonio Torres; Identity; Memory; Migration; Space